2003
DOI: 10.1016/s0378-1097(03)00021-1
|View full text |Cite
|
Sign up to set email alerts
|

A new method for rapid screening of bacterial species- or subspecies-specific DNA probes

Abstract: A simple assay for the rapid screening of bacterial species-or subspecies-specific DNA probes for the random cloning method is presented, involving the use of genomic DNAs as probes and recombinant plasmid DNAs containing genomic DNA digested with HindIII as targets. The optimal amount of target DNAs and the concentration of digoxigenin-labeled genomic DNA probes were 20 ng and 100 ng ml 31 (or 10 ng and 200 ng ml 31 ), respectively. The method was applied to the development of Fusobacterium nucleatum subspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…nucleatum ATCC 25586 T (25); the genomic DNA nucleotide sequence of this strain shows that it can produce only three amino acids (glutamate, aspartate, and asparagine) and several amino acids or peptide transporter proteins (18). Considering this, it appears that the zinc protease of F. nucleatum plays a role in dissociating proteins or peptides within the dental plaque matrix, making them available in their cytoplasm.…”
Section: Vol 48 2010 Discrimination Of F Nucleatum Subspecies 549mentioning
confidence: 99%
See 1 more Smart Citation
“…nucleatum ATCC 25586 T (25); the genomic DNA nucleotide sequence of this strain shows that it can produce only three amino acids (glutamate, aspartate, and asparagine) and several amino acids or peptide transporter proteins (18). Considering this, it appears that the zinc protease of F. nucleatum plays a role in dissociating proteins or peptides within the dental plaque matrix, making them available in their cytoplasm.…”
Section: Vol 48 2010 Discrimination Of F Nucleatum Subspecies 549mentioning
confidence: 99%
“…nucleatum-specific DNA probe, Fu4, recently was cloned (25). The probe Fu4 (1,268 bp) is composed of the 5Ј end of the partial deoxyuridine 5Ј-triphosphate nucleotidohydrolase (5ЈdUTPase) gene (273 bp out of 441) and the 3Ј end of the partial zinc protease gene (878 bp out of 1,227 bp).…”
mentioning
confidence: 99%
“…2 T by inverted dot blot hybridization (12). The reason for this discrepancy is not immediately clear, but it may be due to the difference in the sensitivity between the two methods.…”
mentioning
confidence: 98%
“…Recently, we introduced a new method for rapid screening of bacterial species-or subspecies-specific DNA probes, named the "inverted dot blot hybridization screening method" (12). In our previous study, the inverted dot blot hybridization data showed that a probe, Pi30, was specific for P. intermedia (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation